2021
DOI: 10.1186/s13613-021-00910-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-intensive care syndrome after a critical COVID-19: cohort study from a Belgian follow-up clinic

Abstract: Purpose Many patients with coronavirus disease 2019 (COVID-19) required critical care. Mid-term outcomes of the survivors need to be assessed. The objective of this single-center cohort study was to describe their physical, cognitive, psychological, and biological outcomes at 3 months following intensive care unit (ICU)-discharge (M3). Patients and methods All COVID-19 adults who survived an ICU stay ≥ 7 days and attended the M3 consultation at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 29 publications
(31 reference statements)
6
63
2
7
Order By: Relevance
“…Follow-up data in more recent studies has highlighted the potential for COVID-19 to be associated with prolonged, multisystem involvement associated with significant disability, 22 with considerable reduction in functioning and quality of life among individuals who have received intensive care treatment. 23 A significant proportion of people who have received intensive care treatment for COVID-19 have post-intensive care syndrome characterised by physical and cognitive impairments and problems with mental health. 24 This could explain the increasing rates of threads related to intensive care treatment due to forum users’ concerns of the potential need for intensive care treatment, raising questions about family members or friends currently receiving intensive care treatment, or in relation to problems faced after being discharged from the intensive care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up data in more recent studies has highlighted the potential for COVID-19 to be associated with prolonged, multisystem involvement associated with significant disability, 22 with considerable reduction in functioning and quality of life among individuals who have received intensive care treatment. 23 A significant proportion of people who have received intensive care treatment for COVID-19 have post-intensive care syndrome characterised by physical and cognitive impairments and problems with mental health. 24 This could explain the increasing rates of threads related to intensive care treatment due to forum users’ concerns of the potential need for intensive care treatment, raising questions about family members or friends currently receiving intensive care treatment, or in relation to problems faced after being discharged from the intensive care setting.…”
Section: Discussionmentioning
confidence: 99%
“…There are already expressed fears that post-COVID-19 PICS will overwhelm healthcare facilities designed and available for post-ICU rehabilitation [130]. Multiple centers are creating multidisciplinary programs for the post-COVID-19 population [131,132]. Authors report that the physical, psychological and cognitive impairments observed in post-COVID-19 ICU survivors were comparable to those observed in non-COVID-19 patients [133].…”
Section: Covid-19-related Picsmentioning
confidence: 99%
“…Moreover, patients who underwent ICU admission for COVID-19 related ARDS (C-ARDS) may also experience post-intensive care syndrome (PICS), which eventually overlaps other symptoms related to COVID-19 itself [9].…”
Section: Introductionmentioning
confidence: 99%